La India de Mircea Eliade: un viaje iniciático - Popeanga, Eugenia (Revista de Filología Románica, 2006)
In 1934, Mircea Eliade publishes in Bucarest a sequence of articles, chronicles and excerpts of a Travel Diary, simply entitled La India. This book contains the existential experience of the young Romanian in an exotic country, as well as his adventure spirit, transforming it all in an initiation journey. The present work presents also a comparison to similar texts about the Asian country (H. Michaux, Pier Paolo Pasolini and Alberto Moravia).